1996
DOI: 10.1021/bi950645p
|View full text |Cite
|
Sign up to set email alerts
|

An NMR Spectroscopy and Molecular Mechanics Study of the Molecular Basis for the Supramolecular Structure of Lipopolysaccharides

Abstract: Lipopolysaccharides from Gram-negative bacteria interact with the mammalian immune system to trigger a cascade of physiological events leading to a shock syndrome which results in the death in over 70% of cases of severe shock. It is known that the supramolecular structures of lipopolysaccharide aggregates are critical contributors to their biological activities. Despite this, the molecular basis for the formation if the regular hexagonal plates and arrays observed in lipopolysaccharide films and suspensions i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
25
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 27 publications
1
25
0
Order By: Relevance
“…A similar conclusion is supported by modeling that indicates that a single LPS molecule, viewed from above, is shaped like a triangular wedge or pie slice (64). Six such molecules can self-associate with their points facing inward to form a circular hexamer, and multiple hexamers can form a regular hexagonal lattice held together by divalent cations (27,64). Brandenburg and Wiese reemphasize the importance of these interactions, although they believe that the aqueous gaps between the LPS hexamers might not be favored in vivo (2).…”
mentioning
confidence: 55%
See 2 more Smart Citations
“…A similar conclusion is supported by modeling that indicates that a single LPS molecule, viewed from above, is shaped like a triangular wedge or pie slice (64). Six such molecules can self-associate with their points facing inward to form a circular hexamer, and multiple hexamers can form a regular hexagonal lattice held together by divalent cations (27,64). Brandenburg and Wiese reemphasize the importance of these interactions, although they believe that the aqueous gaps between the LPS hexamers might not be favored in vivo (2).…”
mentioning
confidence: 55%
“…The authors concluded that the variety of intermolecular contacts would allow the O polysaccharide to self-assemble as "a mechanically stable, feltlike network" (23). A similar conclusion is supported by modeling that indicates that a single LPS molecule, viewed from above, is shaped like a triangular wedge or pie slice (64). Six such molecules can self-associate with their points facing inward to form a circular hexamer, and multiple hexamers can form a regular hexagonal lattice held together by divalent cations (27,64).…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…On the other hand, NMR spectroscopy can provide information on the covalent structure and the complex conformational equilibria of oligosaccharides in solution [46,47,64,[77][78][79]. Moreover, it is the only available technique that can determine both the anomericities and linkages of a novel glycan.…”
Section: Structural Characterization Of Polysacchridesmentioning
confidence: 99%
“…The LPS form macromolecular aggregates in vitro (2,3,33).The fluidity (order-disorder conformation) in the hydrocarbon chains of LPS aggregates was measured. The fluorescent dye pyrene, a probe for lipid fluidity (10,32), was used.…”
mentioning
confidence: 99%